Rewrite the equation by completing the square:
![(2x + 9)^2 = (53)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wywezemjytixcw18a12xy2h63t4adm0syo.png)
Solution:
Given that,
![2x^2 - 9x + 7 = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/eruogqy72fovbnnkeh4vsh8bkcjexvqbi2.png)
We have to rewrite by completing the square
Step 1:
The general quadratic equation is given as:
![ax^2 + bx + c = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h2uc4zsixfbrtp6lrt3j5pcdjdem1f3bsp.png)
Compare with given, we get,
a = 2
b = -9
c = 7
Step 2:
From given,
![2x^2 - 9x + 7 = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/eruogqy72fovbnnkeh4vsh8bkcjexvqbi2.png)
Subtract 7 from both sides,
![2x^2 - 9x = -7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/b9f5mek0txmnxv6xoihd7s51lmf4wgzhbh.png)
Step 3:
Find square of half of b
![((b)/(2))^2 =( (-9)/(2))^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1uwy1ovrak2eilnqt8q4f8lt18udtggfk6.png)
Add the term to each side of equation
![2x^2 - 9x + ((-9)/(2))^2= -7 + ((-9)/(2))^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/dgl081srer5w0k2buhxw6db7onnws5uvq4.png)
Simplify
![2x^2 - 9x + ((9)/(2))^2= -7 + (81)/(4)\\\\2x^2 - 9x + ((9)/(2))^2= (53)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/s9a5o938oed9g6voi8cm9avrdyhd6fjjb6.png)
The left side is of form:
![(a-b)^2 = a^2 - 2ab + b^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/brlykzpe2lwn3uamw2ltd7klwncw8y8x2s.png)
Therefore,
![(2x + 9)^2 = (53)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wywezemjytixcw18a12xy2h63t4adm0syo.png)
Thus the solution is found